Analisis Kandungan Besi (Fe) dan Magnesium (Mg) dalam Bijih Besi di Daerah Abai Sangir Kabupaten Solok Selatan Secara Spektrofotometri Serapan Atom - Elvira Julita; Zul Afkar; Iryani Ahmad (Jurnal Periodic Jurusan Kimia UNP, 2012)
Has done research on the determination of iron content (Fe) and magnesium (Mg) in the iron ore Atomic Absorption Spectrophotometric. This study aims to determine the best type of solvent and solvent volume best with ≤ 63μm particle size in determining the content of iron (Fe) and magnesium (Mg) by Atomic Absorption Spectrophotometric and to determine the content of iron (Fe) and magnesium (Mg) in the ore ore. Iron and magnesium content analysis performed by using the method of destruction of wet and conducted some of the variation of solvent variation: concentrated HCl, concentrated HNO3 and HCl - HNO3 concentrated (3:1) or aquaregia as well as the best solvent volume variation is 15 mL, 25 mL, 35 mL , 45 mL and 60 mL. The results showed that the highest iron content obtained by using 25 ml of HCl solvent that is 48.551% at particle size ≤ 63μm and high magnesium levels obtained using 35 mL of solvent aquaregia is 0027% at a particle size ≤ 63 μm.